2014
DOI: 10.1016/j.jphotochem.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of 3-methylbutanal and trimethylamine with combined plasma and photocatalysis in a continuous planar reactor

Abstract: International audienceThis paper deals with the 3-methylbutanal ((CH3)2CHCH2COH) removal with the help of a nonthermal surface plasma discharge coupled with photocatalysis. The capability of this process for gas treatment was studied. A planar reactor system was developed in order to perform the effect of adding photocatalytic material in plasma surface discharge barrier dielectric (SDBD) zone on (i) 3-methylbutanal removal, (ii) selectivity of CO2 and CO, (iii) byproducts formation such ozone formation. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
7
15
0
Order By: Relevance
“…This means that ozone acts not only as an electron acceptor, but also as a source to generate hydroxyl radicals in the UV/O 3 process . Presumably plasma itself can generate UV irradiation . However, it was found that the influence of the UV light generated by the plasma reactor was very low .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that ozone acts not only as an electron acceptor, but also as a source to generate hydroxyl radicals in the UV/O 3 process . Presumably plasma itself can generate UV irradiation . However, it was found that the influence of the UV light generated by the plasma reactor was very low .…”
Section: Resultsmentioning
confidence: 99%
“…Presumably plasma itself can generate UV irradiation . However, it was found that the influence of the UV light generated by the plasma reactor was very low . Another study proved that, in atmospheric air, the photocatalytic decomposition rate of acetaldehyde by the UV light of plasma is lower than 0.2 % of the decomposition rate of the plasma itself .…”
Section: Resultsmentioning
confidence: 99%
“…Atmospheric VOCs can be generated by variety of industrial and commercial activities such as oil supplying, transportation, use of paints, polymers synthesis, metal degreasing, domestic activities, etc. (Arfaeinia et al, 2015;Assadi et al, 2014;Barzegar et al, 2014). Exposure to VOCs might cause headache, fatigue, irritation of respiratory tract, dizziness and nausea, skin irritation, rhinitis, and also toxic effects to the nervous system (Auvinen and Wirtanen, 2008;Mirzaei, 2016;Mo et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In this technique, a semi-conductor photocatalyst is activated by photons generated by a UV radiation lamp (sunlight or UV lamps) (Assadi et al, 2013;Bouzaza et al, 2006). It is proved that this technique has the ability to abate a large number of VOCs with a low energy consumption (Assadi et al, 2014;Pichat et al, 2000). Therefore, it seems to be a suitable method for treatment of air polluted by VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these limitations, many attempts have been made and have engendered the development of a hybrid system using multiple techniques such as packed bed NTP reactors [16,17], NTP/electrostatic precipitation [18], NTP/catalysis [19,20], photocatalysis [21] and adsorption/NTP [22]. Among these VOC removal techniques, the combination of non-thermal plasma with catalysts/sorbents, i.e., plasma-catalysis, is remarkably investigated during the last decade because of their improved performance such as increased energy efficiency and suppressed unwanted This could also be an effective regeneration technique compared to conventional techniques like thermal treatment, which often leads to catalytic deactivation owing to particle agglomerations on catalyst surfaces and poses high a cost.…”
Section: Introductionmentioning
confidence: 99%